Temperature-induced sign reversal of biaxiality observed by conoscopy in some ferroelectric Sm- C* liquid crystals - FUKUDA, ATSUO; VIJ, JAGDISH KUMAR (My University, 2007)
We have studied various ferroelectric liquid crystals to find the average molecular direction of the shortest axis in the perfectly unwound state by using tilted conoscopic measurements. We find that there exist two types of temperature dependencies of the biaxiality. Some materials exhibit increasing biaxiality while others show decreasing biaxiality with increasing temperature. The former shows a temperature-induced sign reversal of biaxiality. Three different physical mechanisms are identified as responsible for the emergence of biaxiality: (i) anisotropic fluctuations of the long molecular axis, (ii) a biased rotation around the long axis, and (iii) the local field effect. By means of a simple theoretical investigation, we conclude that these two types of trends are due mainly to the opposite signs of the biaxial order parameter C, which represents the second mechanism: the biased rotation around the long axis. This means that the central phenyl planes of molecules belonging to materials having biaxiality that increases with temperature are oriented on the average parallel to the tilt plane (the shortest index of refraction axis normal to the tilt plane), and, on the contrary, in those of the others molecules are oriented perpendicular to the tilt plane (the shortest index of refraction axis lying in the tilt plane). Thus, the direction of the phenyl ring plane of the liquid crystal molecules determines the different temperature dependencies of the biaxiality. It is also shown that the phenomenon of sign reversal of the biaxiality is due to the competitive contributions of the first and second physical mechanisms.
PUBLISHED
Article number 011709
Keywords: Electronic & Electrical Engineering